Tantangan Komunikasi Pemasaran Terpadu Industri Perhotelan di Era Digital - Alif Sioux Ramli; Jokhanan Kristiyono (Persatuan Wartawan Indonesia, 2023)
The Covid-19 pandemic caused the hotel accommodation economy to stop, forcing 1,504 hotels across Indonesia to close. This situation forces hotel accommodation to innovate, by designing a recovery strategy until it arrives in the post-covid-19 pandemic. The right recovery strategy to develop is a marketing strategy, in order to increase motivation and be able to develop the company. Marketing Communication Mix is a marketing strategy that is often used by companies. In this study the researchers discussed